Noise annoyance during COVID-19 lockdown: A research of public opinion before and during the pandemic - Şentop Dümen, Ayça; Şaher, Konca (My University, 2020)
Strict lockdown strategies to stop the spread of COVID-19 have caused a decrease in environmental noise levels and introduced new noise conditions in dwellings. The present study has investigated the impact of the forced lockdown in Turkey on noise annoyances due to traffic, neighbors, and personal dwellings, as well as the concern of being heard by neighbors, and overall dwelling satisfaction in an online questionnaire. The stress and anxiety levels of respondents were also investigated. The survey obtained 1053 respondents. Additionally, environmental noise levels were measured over 24-h at two locations and compared with results before the pandemic. The results clearly exhibit that environmental noise levels and annoyance due to the noise levels dropped significantly. The annoyance drop was larger in previously noisier environments than previously tranquil locations. Noise annoyance due to neighbor noise did not change significantly; however, noise annoyance due to one's own dwelling increased. The results also confirmed an overall increase in dwelling satisfactions indicating a correlation between dwelling satisfaction and lower environmental noise levels. Although the results confirmed that noise annoyance was positively correlated with stress and anxiety levels, the change of annoyance between before and during lockdown was shown to be independent from the stress and anxiety level.